The Viracopos International Airport and its induction to the development of the Campinas Metropolitan Region-SP - Cappa, josmar; sperancini, josé henrique souza bassi; Struchel, Andrea (Geografares, 2014)
We analysed how the municipalities of the Metropolitan Region of Campinas (MRC) established public policies to internalise the economic potential of Viracopos International Airport. Public Law and Regional Economic benchmarks were used to analyse the Master Plans of the nineteen municipalities of the MRC and their relationships with Viracopos International Airport. There is a lack of systemic vision in transport as an activity that adds value to commodities, in addition to interactions with transportation projects of the Union, the state and the municipalities in the region. It is necessary to have a Metropolitan Master Plan so as not to compromise strategic regional development projects, and to broaden the multiplier effects of employment, income and taxes.
Keywords: Public Policies; Regional and Local Development; Air Transport and Airports